SAM LUBELL, DOUGLAS WOODS - Julius Shulman Los Angeles - Fava, Nadia (ZARCH, 2013)
SAM LUBELL, DOUGLAS WOODSJulius Shulman Los Angeles. The Birth of a Modern MetropolisNueva York: Rizzoli, 2011, 239 págs. Idioma: inglés